(untitled) (ABDIMAS: Jurnal Pengabdian Masyarakat, 2026)
Cardiovascular health is a crucial aspect of maintaining quality of life in the elderly, especially considering the increased risk of hypertension with age. Elderly caregivers (pramuwerdha) play a strategic role in implementing health programs as companions to the elderly, yet their knowledge of hypertension management remains limited. This community service initiative aims to enhance the knowledge and skills of elderly caregivers in facilitating heart-healthy exercise as a non-pharmacological intervention for hypertension management in the elderly. The activity was conducted at the Karawang Elderly Home Service Unit for 3 days in June 2025, using a quasi-experimental design with a one-group pretest-posttest approach. Implementation methods included hypertension screening, pre-test, education, and heart-healthy exercise demonstration. A total of 6 caregivers and 24 elderly participants took part in this activity. Results showed a significant increase in caregiver knowledge from an average pretest score of 5.96 to 8.10 on the posttest (35.9% increase, p=0.005). Among the elderly, there was a decrease in systolic blood pressure from 154.6 mmHg to 142.1 mmHg and diastolic from 94.8 mmHg to 86.3 mmHg (p<0.05). This community service demonstrates the effectiveness of heart-healthy exercise training in enhancing the capacity of caregivers as agents of change in elderly hypertension management. It is expected that caregivers can actively facilitate heart-healthy exercise activities to improve the quality of life of the elderly.